The effects of social media and event marketing on brand awareness in a culturally positioned MSME: Evidence from Kedai Rasta - Timothy Andrianus Philemon; Ribka Trivena Muabuai (Universitas Nusa Cendana, 2026)
This study examines how social media marketing (SMM) and event marketing (EM) contribute to brand awareness for Kedai Rasta, a culturally grounded MSME based in Bandung. The central premise is that cultural identity, when strategically mobilised, can function as a meaningful branding resource that shapes how both digital and experiential marketing activities build brand visibility. Using a quantitative cross-sectional design, data were collected from consumers through Likert-scale questionnaires and analysed via multiple linear regression. The results confirm that both SMM and EM are positively and significantly associated with brand awareness, though each operates through distinct pathways. Social media marketing strengthens awareness primarily through content quality and audience connection, while event marketing works largely through direct consumer involvement and immersive experiential engagement. Dimensions related to interaction intensity showed comparatively limited influence in both channels, pointing to communication barriers that restrict broader audience reach and slow message diffusion beyond existing communities. The study further finds that cultural identity plays a dual role. Rather than functioning straightforwardly as an asset, it acts as both an enabling and a bounding resource, amplifying brand awareness when translated into shareable digital content and immersive offline experiences, yet narrowing its reach when interactions remain concentrated within culturally homogeneous groups. These findings contribute to literature on SME branding, cultural marketing, and integrated marketing communications by underscoring the value of pairing culturally distinctive online content with well-designed experiential marketing as mutually reinforcing elements of a coherent brand strategy. Future research would benefit from multi-firm, longitudinal, or experimental designs, and from incorporating digital analytics and behavioural indicators alongside self-reported measures to develop a more comprehensive understanding of brand awareness formation in culturally oriented enterprises. Keywords: Social Media Marketing; Event Marketing; Brand Awareness; MSME; Cultural Branding